Analisis Karakteristik Sosial-Ekonomi Petani Sayuran dalam Akses Kredit Mikro di Desa Cikidang, Kabupaten Bandung Barat - Syafa'at, Iin Aulia Syafira; Nidar, Sulaeman Rahman; Mulyana, Asep (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Microcredit plays a crucial role in supporting agricultural development, particularly for smallholder farmers. This study aims to analyze the influence of socio-economic characteristics on vegetable farmers' access to formal and informal microcredit in Cikidang Village. Using a quantitative method with a survey approach, data were collected through questionnaires from 100 respondents selected via purposive sampling. Descriptive analysis revealed that the majority of farmers accessing formal microcredit (66%) had higher education levels (6% were university graduates), monthly incomes ranging from IDR 5,000,000 to IDR 10,000,000 (51%), and landholdings exceeding 1 hectare (33%). Conversely, informal microcredit (34%) was predominantly accessed by farmers with lower education levels (59% elementary school graduates), incomes below IDR 5,000,000 (76%), and landholdings under 1 hectare (97%). These findings highlight that socio-economic limitations restrict farmers' access to formal credit, necessitating inclusive policies such as simplified procedures, elimination of collateral requirements, and enhanced financial literacy to improve access to formal microcredit and support sustainable farming practices.